Pengaruh Penerapan Pendidikan Multikultural pada Mata Pelajaran PPKN terhadap Sikap Sosial Siswa SMA Labschool Unsyiah Banda Aceh - Fernanda, Indah Nur; Ruslan, Ruslan; Yunus, Muhammmad (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2024)
Multicultural education is an approach to education that recognizes and respects the diversity of cultures, ethnicities and social backgrounds in the learning process. This research aims to identify the influence of implementing multicultural education on students' social attitudes at SMA Labschool Unsyiah Banda Aceh. This research method uses a quantitative approach using correlational research, data collection techniques through distributing questionnaires to the research sample, namely all class XI students. The results of the research show that there is an influence between the application of multicultural education on the social attitudes of SMA Labschool Unsiyah Banda Aceh with a determination coefficient of 0.156 so that students' social attitudes are influenced by the application of multicultural education by 15.6%. The rest is influenced by other factors outside research. This research also identifies several challenges in implementing multicultural education, such as challenges in integrating multicultural education into the wider education system. Thus, the findings of this research provide a better understanding of the importance of implementing multicultural education in creating a comprehensive learning environment and supporting student development in facing an increasingly global and diverse society.